Tinjauan Yuridis Perjanjian Franchise Dengan Konsep Mudharabah (Studi Kasus Ayam Penyet Surabaya Cabang Surakarta) - Algabimanyu, Fath; , Mutimatun Ni'ami, S.H., M.Hum (2016)
Franchise/ Franchising is an engagement/agreement between the two parties. As the agreement can be ensured all the provisions of civil law (Civil Code) of the agreement (Article 1313), which is an act by which one or more persons to bind himself to the others. The concept of franchise business lately has become one of the limelight as a form of business development breakthrough. Given that franchised businesses are businesses that have been tested and successful in their fields, so it is considered to be "guarantees" profit, these factors then become a "magnet" to attract the interest of society at large. Through franchising concept one does not need to start a business from scratch, because there have been integrated in the franchise system, which allows a franchisee to run the business properly.